GEOCHEMISTRY OF REDUCED FLUIDS FROM ALKALINE IGNEOUS ROCKS OF THE KHIBINY PLUTON - Gottikh R.P.; Pisotskii B.I.; Kulakova I.I. (My University, 2006)
The first sweeping generalizations on gas compositions in nepheline syenite, trachytoid khibinite, ijoliteurtite, rischorrite, malignite, lujavrite, foyaite, and apatite–nepheline ores were been carried out by Petersil’e and Ikorskii, who showed that methane (as much as 93%), carbon oxide, and hydrogen are sharply predominant in occluded and free gases, whereas homologs of methane and carbon oxide are subordinate. The subsequent investigations of gas contents in particular minerals in typical igneous rocks of the Lovozero and Khibiny plutons have demonstrated nonuniform distribution of reduced components in minerals on the one hand, and confinement of their highest concentrations to certain mineral species on the other.
Keywords: gas compositions; nepheline syenite; trachytoid khibinite; ijoliteurtite; Khibiny pluton